Patterns of regional economic decline and growth : the past and what has been happening lately - Perlman, Mark (Washington : American Enterprise Institute for Public Policy Research, 1982)
This is one of several papers that have developed from the American Enterprise Institute. Although for the past half century emphasis has been placed on national level policies for economic growth in the United States, economic decentralism is not a new idea. Each state has both history and an evolving political and economic decision making capability for sustaining and expanding its wealth consuming and wealth producing capabilities.
Includes bibliographical references.
nmn / 11-6-2021
Loans
Keywords: Economic conditions; Regional disparities; United States